The seed and agricultural biotechnology industries in India: An analysis of industry structure, competition, and policy options - Spielman, David J.; Kolady, Deepthi Elizabeth; Chandrasekhara Rao, N.; Cavalieri, Anthony J. (International Food Policy Research Institute, 2011)
Since the late 1980s, technological advances and policy reforms have opened up new opportunities for growth in India's seed and agricultural biotechnology industries. The impacts of such changes have been significant in India's cotton sector, but less so for the country's main cereal crops, where both yield and output growth rates have been relatively stagnant. Some public policymakers and corporate decisionmakers are confident that the private sector will help reverse these trends, arguing that the right combination of new technological solutions and progressive policy reforms will unleash a significant increase in private investment in productivity-enhancing products and services. The structure of India's seed and agbiotech industries, as well as the policies designed to support their growth, will be a significant determinant of this expected impact. This paper examines the structure of India's cereal seed and agbiotech industries, its potential effects on innovation and social welfare, and the policies that may improve both industry performance and the delivery of new technologies to resource-poor, small-scale farmers in India's cereal production systems. We focus our analysis on indicators and scenarios within India's agricultural innovation market for improved seed and agricultural biotechnology products. This market includes firms engaged in the development, commercialization, and marketing of new seed-based technologies; it is characterized by a high level of knowledge intensity, relatively high levels of R&D investment, significant barriers to entry, significant levels of regulation, and relatively few products in the market. And it is within this market that factors such as strategic corporate behavior and public policy can affect the balance between a socially desirable rate of innovation, on the one hand, and a socially desirable distribution of the gains from innovation among consumers, farmers, and innovators, on the other hand.